2018
DOI: 10.1007/s11306-018-1457-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analyses reveal lipid abnormalities and hepatic dysfunction in non-human primate model for Yersinia pestis

Abstract: IntroductionPneumonic plague is caused by the aerosolized form of Yersinia pestis and is a highly virulent infection with complex clinical consequences, and without treatment, the fatality rate approaches 100%. The exact mechanisms of disease progression are unclear, with limited work done using metabolite profiling to study disease progression.ObjectiveThe aim of this pilot study was to profile the plasma metabolomics in an animal model of Y. pestis infection.MethodsIn this study, African Green monkeys were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The 46 analytes that were detected in our macaques and the normal ranges determined by analysis of plasma from 39 healthy Rhesus macaques, are shown in Table 1 . Although these MAPs are designed for human samples, Myriad RBM assays have been previously used for successful analysis of non-human primate inflammation and neurological disease ( Byrnes-Blake et al., 2012 ; Dietsch et al., 2015 ; Gautam et al., 2018 ; Kobayashi et al., 2013 ; Olsen et al., 2010 ; Shen et al., 2016 ). However, for analytes with all undetectable readings, these may either be due to lack of cross-reactivity or the absence of those molecules in the samples tested.…”
Section: Methodsmentioning
confidence: 99%
“…The 46 analytes that were detected in our macaques and the normal ranges determined by analysis of plasma from 39 healthy Rhesus macaques, are shown in Table 1 . Although these MAPs are designed for human samples, Myriad RBM assays have been previously used for successful analysis of non-human primate inflammation and neurological disease ( Byrnes-Blake et al., 2012 ; Dietsch et al., 2015 ; Gautam et al., 2018 ; Kobayashi et al., 2013 ; Olsen et al., 2010 ; Shen et al., 2016 ). However, for analytes with all undetectable readings, these may either be due to lack of cross-reactivity or the absence of those molecules in the samples tested.…”
Section: Methodsmentioning
confidence: 99%
“…al. 22 . The abundances of metabolites in cluster 3 were elevated in both the Lm and Cr groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gautam et al. conducted an untargeted metabolomics analysis of plasma obtained from African Green monkeys infected with a highly virulent, aerosolized Yersinia pestis strain CO92 and observed that the concentration of lysophospholipids, including 1‐oleoylglycerophosphoethanolamine, was significantly reduced compared to the control group 36 . Lysophospholipids, generated through the metabolism and disruption of biological membranes, are crucial players in cellular stress signalling, inflammation, resolution and host defence responses 37 .…”
Section: Discussionmentioning
confidence: 99%
“…analysis of plasma obtained from African Green monkeys infected with a highly virulent, aerosolized Yersinia pestis strain CO92 and observed that the concentration of lysophospholipids, including 1-oleoylglycerophosphoethanolamine, was significantly reduced compared to the control group. 36 Lysophospholipids, generated through the metabolism and disruption of biological membranes, are crucial players in cellular stress signalling, inflammation, resolution and host defence responses. 37 In vitro investigations have demonstrated that lysophospholipid metabolism modulates the inflammatory response in sepsis by promoting Toll-like receptor 4 (TLR 4) membrane translocation.…”
Section: F I G U R Ementioning
confidence: 99%